Hindrances for Settlement: ASEAN’s Difficulties in Dealing with the South China Sea Dispute - Manullang, Abel Josafat (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 3 No 1 (2023): JURNAL DIKSHI, 2023)
As one of the thriving regions in the world, it is no surprise that Southeast Asia has met numerous problems as part of its development. One of which being the South China Sea dispute, a conflict that has yet to be solved either by the claimant states or notably ASEAN as the regional actor. To this matter, the writer seeks to explain what has been preventing ASEAN from making an effective move to the dispute. Through the use of qualitative research methods and incorporating the secondary data, the author seeks to explain the answers to the aforementioned guiding question. In the article, the writer explains in depth the three hindrances ASEAN is being faced with in regard to responding to the South China Sea dispute. First, China has proven to be an important actor in the entire scheme of the dispute, not only as a claimant state but also as a neighbor to the ASEAN member states. Such characteristic of China affects the ASEAN heavily as it worsens the apparent disunity ASEAN member states are facing in responding together to the dispute. Moreover, ASEAN must also take the outside parties, notably the US, into proper considerations in deciding its course of action.